Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2021)
As the 27th ORNAC National Conference, now a virtual conference, draws near there is both trepidation and excitement relating to the outcome with this new conference delivery platform and what will it mean for the future.